Elizur Wright papers - Wright, Elizur, 1804-1885.
Correspondence, manuscript and typewritten transcripts of writings, legal and financial papers, scrapbooks, clippings, printed material, photographs, and other papers relating chiefly to Wright's involvement in the antislavery movement and to his work as an actuary and as an author and translator. Documents his work with organizations including the American Anti-Slavery Society and its publication The Quarterly Anti-Slavery Magazine, Massachusetts Anti-Slavery Society and its publication The Massachusetts Abolitionist, and the National Liberal League. Subjects include abolition, actuarial science, antimasonry, conservation, free thought, 19th century politics, reform movements, religion, temperance, the tobacco habit, and family affairs.
Correspondents include Wright family members and Francis Ellingwood Abbot, Louisa May Alcott, May Alcott, De Robigne Mortimer Bennett, Catherine H. Birney, James Gillespie Birney, William Birney, Henry Browne Blackwell, William Henry Burleigh, Salmon P. Chase, Charles A. Dana, Joshua N. Danforth, William Lloyd Garrison, Horace Greeley, Beriah Green, Sallie Holley, Robert Green Ingersoll, Simeon Smith Jocelyn, Amos A. Phelps, Wendell Phillips, Albert L. Rawson, Gerrit Smith, Henry B. Stanton, Lewis Tappan, Theodore Dwight Weld, and John Greenleaf Whittier.
Reformer, publisher, and actuary.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbot, Francis Ellingwood, -- 1836-1903 -- Correspondence; Alcott, Louisa May, -- 1832-1888 -- Correspondence; Alcott, May, -- 1840-1879 -- Correspondence; Bennett, De Robigne Mortimer, -- 1818-1882 -- Correspondence; Birney, Catherine H. -- Correspondence; Birney, James Gillespie, -- 1792-1857 -- Correspondence; Birney, William, -- 1819-1907 -- Correspondence; Blackwell, Henry Browne, -- 1825-1909 -- Correspondence; Burleigh, William Henry, -- 1812-1871 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Dana, Charles A. -- 1819-1897 -- Correspondence; Danforth, Joshua N. -- 1798-1861 -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Green, Beriah, -- 1795-1874 -- Correspondence; Holley, Sallie, -- 1818-1893 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Jocelyn, Simeon Smith, -- 1799-1879 -- Correspondence; Phelps, Amos A. -- 1805-1847 -- Correspondence; Phillips, Wendell, -- 1811-1884 -- Correspondence; Rawson, Albert L. -- 1829-1902 -- Correspondence; Smith, Gerrit, -- 1797-1874 -- Correspondence; Stanton, Henry B. -- 1805-1887 -- Correspondence; Tappan, Lewis, -- 1788-1873 -- Correspondence; Weld, Theodore Dwight, -- 1803-1895 -- Correspondence; Whittier, John Greenleaf, -- 1807-1892 -- Correspondence; Wright family; Wright family -- Correspondence; American Anti-Slavery Society; Massachusetts Anti-Slavery Society; National Liberal League; Massachusetts abolitionist; Quarterly anti-slavery magazine; Antislavery movements; Conservation of natural resources; Free thought; Freemasonry; Insurance -- Mathematics; Religion; Slavery -- United States; Social problems; Temperance; Tobacco use; United States -- Politics and government -- 19th century; Actuaries; Publishers; Reformers